2019
DOI: 10.1111/cea.13487
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective markers of paediatric atopic dermatitis persistence after hospital diagnosis: A nationwide cohort study

Abstract: Background Atopic dermatitis (AD) normally onsets in childhood and mostly resolves before adolescences. Disease persistence is known to be difficult to study properly, and current predictors are insufficient to identify more than a small fraction of patients at risk. Objective To study personal AD medicine history as a retrospective marker of persistent AD. Methods The study population included all Danish first hospital contacts with a diagnosis of AD (ICD‐10, L20) between 1995 and 2012. National register data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…24, 25 We identified visits based on the primary International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) code on the visit (listed in Appendix Table 1). [26][27][28][29][30][31][32][33] Consistent with prior work, the ARTI condition group is composed of both bacterial and viral diagnoses including sinusitis, acute otitis media, streptococcal pharyngitis, viral upper respiratory infection, bronchiolitis, and others. 26 Gastroenteritis also included both viral and bacterial etiologies.…”
Section: Diagnoses and Vaccine Identificationmentioning
confidence: 91%
“…24, 25 We identified visits based on the primary International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) code on the visit (listed in Appendix Table 1). [26][27][28][29][30][31][32][33] Consistent with prior work, the ARTI condition group is composed of both bacterial and viral diagnoses including sinusitis, acute otitis media, streptococcal pharyngitis, viral upper respiratory infection, bronchiolitis, and others. 26 Gastroenteritis also included both viral and bacterial etiologies.…”
Section: Diagnoses and Vaccine Identificationmentioning
confidence: 91%
“…3 We recently showed that medication use could predict AD persistence in children. 4 It may therefore be speculated that early identification of children with increased risk of severe and persistent disease course could improve disease management and reduce the burden of AD.…”
Section: Introductionmentioning
confidence: 99%
“…A decline in secondary healthcare resource use following index date was observed in the present study and may indicate that patients' symptoms improved over time, potentially through successful treatment regimens or spontaneous resolution of the disease in some patients. However, a recent study [34] shows that disease persistence is high and that the decline in healthcare resource use may be a consequence of patients being returned to primary care for continuous management (and thus are not captured in the present study). The evolution of costs over time suggests that healthcare resource use is the most intense in the short term after onset of the disease or at relapse of symptoms.…”
Section: Discussionmentioning
confidence: 84%